1992
DOI: 10.1002/syn.890110406
|View full text |Cite
|
Sign up to set email alerts
|

Induction of long‐term potentiation in the basolateral amygdala does not depend on NMDA receptor activation

Abstract: Long-term potentiation (LTP) can be induced in the lateral and basolateral amygdala by stimulating synaptic afferents in the external capsule (EC). We examined the sensitivity of amygdaloid LTP to the NMDA receptor antagonist 2-amino-5-phosphonopentanoate (AP5), which is known to block LTP induction in the Schaffer collateral/CA1 synapses in the hippocampus. While relatively high concentrations (100 microM) of DL-AP5 were effective in preventing LTP induction in the lateral and basolateral amygdala in vitro, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
70
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(76 citation statements)
references
References 32 publications
5
70
1
Order By: Relevance
“…In support of this possibility concurs the fact that the great majority (93%) of prefrontal-amygdala synapses identified in the BLA are located on dendritic spines of pyramidal projection cells and belong to the asymmetric (excitatory) type (Brinley-Reed et al, 1995). Moreover, EC stimulation has been shown to evoke monosynaptic excitatory postsynaptic potentials (EPSP) in BLA neurons (Chapman and Bellavance, 1992;Li et al, 1998;Mahanty and Sah, 1998;Chapman et al, 1990). Since interneurons represent a minority (o15%) of BLA neurons (McDonald, 1982;Millhouse and De Olmos, 1983), it is unlikely that their firing would have contributed significantly to the generation of the PS.…”
Section: Electrophysiological Experimentssupporting
confidence: 70%
See 3 more Smart Citations
“…In support of this possibility concurs the fact that the great majority (93%) of prefrontal-amygdala synapses identified in the BLA are located on dendritic spines of pyramidal projection cells and belong to the asymmetric (excitatory) type (Brinley-Reed et al, 1995). Moreover, EC stimulation has been shown to evoke monosynaptic excitatory postsynaptic potentials (EPSP) in BLA neurons (Chapman and Bellavance, 1992;Li et al, 1998;Mahanty and Sah, 1998;Chapman et al, 1990). Since interneurons represent a minority (o15%) of BLA neurons (McDonald, 1982;Millhouse and De Olmos, 1983), it is unlikely that their firing would have contributed significantly to the generation of the PS.…”
Section: Electrophysiological Experimentssupporting
confidence: 70%
“…It has been demonstrated that activation of amygdala afferents in the EC (Chapman et al, 1990;Chapman and Bellavance, 1992) or in the LA (Rainnie et al, 1991b) elicit IPSPs that are superimposed or follow the EPSP of BLA neurons referred to above. These IPSPs are GABAergic and are elicited by direct or recurrent activation of local interneurons (Preleviç et al, 1976;Rainnie et al, 1991b); suppressing GABAergic transmission has been shown to result in increased excitability (Wang et al, 2002(Wang et al, , 2001) and epileptiform activity (Chapman et al, 1990; Gean and Shinnick-Gallagher, 1987; Gean et al, 1989).…”
Section: Electrophysiological Experimentsmentioning
confidence: 95%
See 2 more Smart Citations
“…Although the evidence for the importance of LTP in hippocampal function is clearly substantial, LTP is not an exclusive property of the hippocampus. It can be observed in other brain regions including the somatosensory [8,9], visual [35,36], auditory [37], olfactory [11,52], motor [2], piriform [33], entorhinal [17], cingulate [27] cortices, the amygdala [42,10] and thalamo-cortical synapses [13]. Furthermore, a higher elevation of intracellular Ca 2 + levels is associated with LTP and a smaller increase of Ca 2 + is seen when long-term depression (LTD) is induced [3,41].…”
Section: Introductionmentioning
confidence: 99%